Association between branched-chain amino acid levels and gastric cancer risk: large-scale prospective cohort study - Yu, Liang; Bao, Shiming; Zhu, Feng; Xu, Yanyan; Liu, Yanwei; Jiang, Runben; Yang, Chuang; Cao, Feng; Chen, Wei; Li, Pengtao (Frontiers in Nutrition, 2024)
Background Gastric cancer (GC) remains a malignancy with high incidence and mortality rates worldwide. Although branched-chain amino acids (BCAAs) play a crucial role in various physiological and pathological processes, their specific relationship with risk of GC remains unclear.We conducted a large-scale prospective cohort from UK biobank database.We evaluated the relationship between BCAA levels and risk of GC using Cox regression, Kaplan-Meier survival curves, the accelerated failure time (AFT) model, and restricted cubic spline (RCS) analysis.During the follow-up of 12 years, 247,753 participants were included in the study. And the Cox regression analysis revealed that higher levels of isoleucine (HR=0.65, 95% CI 0.48-0.89; P=0.007), leucine (HR=0.57, 95% CI 0.42-0.79; P<0.001), valine (HR=0.53, 95% CI 0.39-0.73; P<0.001), and total BCAAs were associated with a reduced risk of GC (HR=0.51, 95% CI 0.37-0.70; P<0.001).Kaplan-Meier curves and the AFT model confirmed that elevated BCAA levels significantly delayed the onset of GC. Additionally, RCS analysis identified nonlinear dose-response relationships between BCAAs and risk of GC. Stratified analyses indicated that the protective effect of BCAAs was consistent across various subgroups, with a more pronounced impact in older individuals without chronic diseases.Elevated BCAA levels are significantly associated with a reduced risk of GC, particularly in older adults. This finding highlights the potential of BCAAs in GC prevention and suggests that future research and clinical practice should emphasize regulating BCAA levels.